(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Irrational antibiotic therapy is not just about "excessive," unnecessary antibiotics. It also involves the wrong choice of medication, dosage, and/or duration of treatment. The benefits of such "treatment" are questionable, while the harm is evident. An incorrectly chosen drug will not ensure the eradication of the pathogen and/or may increase the risk of side effects for the patient.